2015
DOI: 10.1155/2015/250614
|View full text |Cite
|
Sign up to set email alerts
|

Isolated T Wave Inversion in Lead aVL: An ECG Survey and a Case Report

Abstract: Background. Computerized electrocardiogram (ECG) analysis has been of tremendous help for noncardiologists, but can we rely on it? The importance of ST depression and T wave inversions in lead aVL has not been emphasized and not well recognized across all specialties. Objective. This study's goal was to analyze if there is a discrepancy of interpretation by physicians from different specialties and a computer-generated ECG reading in regard to a TWI in lead aVL. Methods. In this multidisciplinary prospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…The remaining 191 patients constituted the study population and found that T wave inversion in aVL was found to be the only ECG variable signi icantly predicting mid segment (LAD) lesions (Odds Ratio 2.93, 95% Con idence Interval 1.59-5.37, p=0.001. which is totally in agreement to our study , also Hassen GW et al [22]. In a multidisciplinary prospective study, a single ECG with isolated T wave inversion in lead aVL that was interpreted by the computer as normal was given to all participants to interpret in writing.…”
Section: Discussionsupporting
confidence: 93%
“…The remaining 191 patients constituted the study population and found that T wave inversion in aVL was found to be the only ECG variable signi icantly predicting mid segment (LAD) lesions (Odds Ratio 2.93, 95% Con idence Interval 1.59-5.37, p=0.001. which is totally in agreement to our study , also Hassen GW et al [22]. In a multidisciplinary prospective study, a single ECG with isolated T wave inversion in lead aVL that was interpreted by the computer as normal was given to all participants to interpret in writing.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, previous studies reported that approximately 75% of physicians missed an isolated T wave inversion in lead aVL and that the best single lead for the emergency detection of ACS was lead aVL. 12 13 In agreement with this literature, our findings underscore the importance of cautious interpretation of T wave inversion in lead aVL as a clue to predict ischaemic lesions in ACS.…”
Section: Discussionsupporting
confidence: 90%
“…The reasons for the disparities in the diagnostic values among studies are likely multifactorial. First, although the definition of T wave inversion was unclear in previous studies, 5 6 12 we clearly defined T wave inversion according to the AHA definition; 9 therefore, our findings were less likely to be subject to information bias. Second, a previous study used a combination of T wave inversion in lead aVL and lead I to estimate the diagnostic values.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a study by Hassen et al ,6 an ECG, including isolated T-wave inversion in lead aVL, was shown to 191 doctors, and 143 of them (74.9%) interpreted it as normal.…”
Section: Discussionmentioning
confidence: 98%